2022
DOI: 10.1021/acsami.2c12348
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Chemo-/Radioresistance to Boost the Therapeutic Efficacy against Temozolomide-Resistant Glioblastoma

Abstract: Chemo-/radioresistance is the most important reason for the failure of glioblastoma (GBM) treatment. Reversing the chemo-/radioresistance of GBM for boosting therapeutic efficacy is very challenging. Herein, we report a significant decrease in the chemo-/radioresistance of GBM by the in situ generation of SO2 within a tumor, which was released on demand from the prodrug 5-amino-1,3-dihydrobenzo­[c]­thiophene 2,2-dioxide (ATD) loaded on rare-earth-based scintillator nanoparticles (i.e., NaYF4:Ce@NaLuF4:Nd@ATD@D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…To date, focused ultrasound has been used to assist in the delivery of various compounds into the brain, such as nanoparticles, 74 antibodies (e.g., trastuzumab 75 ), chemotherapy drugs (e.g., temozolomide 76 ), nucleotide small interfering RNA (siRNAs), 77 neurotrophins, 78 viral and nonviral vectors 79 . Recent works have demonstrated that focused ultrasound can be used to efficiently deliver nanoprobes or nanomedicine into the brain for imaging of immunosuppressive M 2 − tumor‐associated macrophages in orthotopic glioma, 80 significantly reducing chemo‐/radio‐resistance of glioblastoma, 81 and improving the radiation therapy 82 and immunotherapy of orthotopic glioblastoma 83 . Moreover, the focused ultrasound has been used for the treatment of brain tumors in clinical practice with encouraging results 75 .…”
Section: Design Of Nanoparticles For Crossing the Bbbmentioning
confidence: 99%
“…To date, focused ultrasound has been used to assist in the delivery of various compounds into the brain, such as nanoparticles, 74 antibodies (e.g., trastuzumab 75 ), chemotherapy drugs (e.g., temozolomide 76 ), nucleotide small interfering RNA (siRNAs), 77 neurotrophins, 78 viral and nonviral vectors 79 . Recent works have demonstrated that focused ultrasound can be used to efficiently deliver nanoprobes or nanomedicine into the brain for imaging of immunosuppressive M 2 − tumor‐associated macrophages in orthotopic glioma, 80 significantly reducing chemo‐/radio‐resistance of glioblastoma, 81 and improving the radiation therapy 82 and immunotherapy of orthotopic glioblastoma 83 . Moreover, the focused ultrasound has been used for the treatment of brain tumors in clinical practice with encouraging results 75 .…”
Section: Design Of Nanoparticles For Crossing the Bbbmentioning
confidence: 99%
“…3 Therefore, many strategies have been developed for precise diagnosis and treatment of GBM, including magnetic hyperthermia, 4,5 gene therapy, 6,7 high intensity focused ultrasound therapy, 8,9 immunotherapy 10,11 and gas therapy. 12,13 Recently, modulating the tumor metabolism has emerged as a promising therapeutic strategy. 14,15 In this aspect, the Warburg effect has always been considered as a hallmark of cancer cells, wherein glycolysis is preferred over oxidative phosphorylation even under aerobic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…3 Therefore, many strategies have been developed for precise diagnosis and treatment of GBM, including magnetic hyperthermia, 4,5 gene therapy, 6,7 high intensity focused ultrasound therapy, 8,9 immunotherapy 10,11 and gas therapy. 12,13…”
Section: Introductionmentioning
confidence: 99%
“…To date, a number of strategies have been reported to enhance drug penetration and improve the therapeutic outcome. 14−16 Thus, a vasodilating agent can help overcome this barrier, 17 and when the design incorporates spatiotemporal release of ROS and RNS, then it provides an added control. Nitric oxide (NO), a widely used gasotransmitter, also plays a regulatory role in various biological activities such as vasodilation, cardiac relaxation, inflammatory activities, angiogenesis, and so on.…”
mentioning
confidence: 99%